Strategi Humas Inspiring Agency dalam Membangun Citra Positif Perusahaan di Kalangan Generasi Z - Muharizal Rizki, Aditiya; Aulia, Sisca (Kiwari, 2024)
Image is a very important asset for an organization or company that should be continuously built, maintained and nurtured. Currently, companies operating in the insurance sector are competing to be at the forefront by following developments in information technology. Inspiring Agency is an insurance business unit headed by a Senior Agency Director. The business run by Inspiring Agency is PT Prudential's insurance business. This research aims to determine Inspiring Agency's public relations strategy in building a positive company image among generation Z. In this research the author uses a qualitative approach. The results of this research show that Inspiring Agency continues to strive to create a positive image, socialize its vision, and communicate with the public, especially generation Z. To achieve its goals, Inspiring Agency implements a structured planning strategy. This strategy is an implementation of Inspiring Agency's actions. In its strategy, Inspiring Agency applies publications, events, news, community involvement, image delivery, lobbying and negotiation, and social responsibility. Citra merupakan aset yang sangat penting bagi organisasi atau perusahaan yang semestinya harus terus menerus dibangun, dipelihara, dan dipertahankan. Saat ini perusahaan yang bergerak pada bidang asuransi bersaing menjadi yang tedepan dengan mengikuti perkembangan teknologi informasi. Inspiring Agency adalah salah satu unit bisnis asuransi yang dikepalai oleh Senior Agency Director. Bisnis yang dijalani oleh Inspiring Agency adalah bisnis asuransi PT Prudential. Penelitian ini bertujuan untuk mengetahui strategi humas Inspiring Agency dalam membangun citra positif perusahaan di kalangan generasi Z. Pada penelitian ini penulis menggunakan pendekatan kualitatif. Hasil penelitian ini menunjukkan bahwa Inspiring Agency terus berusaha untuk menciptakan citra positif, mensosialisasikan visinya, dan berkomunikasi dengan masyarakat terutama generasi Z. Untuk mencapai tujuan, Inspiring agency menerapkan strategi perencanaan yang terstruktur. Strategi tersebut merupakan implementasi dari tindakan Inspiring Agency. Dalam strateginya, Inspiring Agency menerapkan publications, event, news, community involvement, inform of image, lobbying and negotiations, dan social responsibility.